Religious houses, violence, and the limits of political consensus in early medieval León (NW Iberia) - Carvajal Castro, Alvaro (Reti Medievali Rivista, 2020)
This paper explores violence against religious houses as an indicator of the limits of political negotiation and consensus building in early medieval polities. It analyses records of attacks against religious houses and clerics from León (NW Iberia) that escape traditional interpreta- tions of violence as a tool in the negotiation of social relations, and construes the events as an ex- pression of local social cleavages. In so doing, it provides a guideline for probing similar records in ways that might illuminate aspects of social relations and dynamics otherwise obscured by the dominant themes of the documentary sources from this period.